Prevalence, diagnosis and treatment in urolithiasis. - Monika Kusz; Adam Alzubedi; Joanna Popiołek; Michał Konopelko (Journal of Education, Health and Sport, 2018)
Kidney stone disease is one of the most common disorders and can be considered a disease systmetic. It occurs in about 5-20 % of all population. Due to the chemical composition of deposits there are several types of kidney stones including calcium oxalate, calcium phosphate, uric acid, magnesium-amonium, phosphate, cysteine. Nephrolithiasis is more common in men than in women. Kidney stones are formed as a result of the crystallization of minerals and their salts. The cause of stone formation in the kidneys also contributes some drugs (such as corticosteroids), hyperparathyroidism, osteoporosis, long-term treatment of peptic ulcer with alkalizing preparations, overdose of vitamin D and improper diet. The most important in treatment of renal colic is relieving pain. Sometimes it is enough to administer analgesics, but sometimes it is necessary to administer strong opioid drugs. Effective medical treatments including thiazide, potassium citrate, acetohydroxamic acid can prevent new stone formation in most patients.